First identification of a patent pentastomid pulmonary (Raillietiella orientalis) infection in a captive Meller's chameleon (Trioceros melleri) in Germany - Paula Sapion-Miranda; David Ebmer; Edwin Kniha; Julia Walochnik; Saskia Dreyer; Dominik Fischer; Lisa Grund; Anja Taubert; Carlos Hermosilla; Malek J. Hallinger (International Journal for Parasitology: Parasites and Wildlife)
A female, zoo-housed, adult Meller's giant one-horned chameleon (Trioceros melleri) showed clinical symptoms including halitosis, obstipation, dysecdysis and shed pentastomid eggs with the faeces. After a patent pentastomiasis was diagnosed, the chameleon's condition worsened after repeated ivermectin treatments, and the animal was euthanized due to animal welfare reasons. The necropsy revealed that the lungs were infected with 29 adult pentastomid specimens. Based on morphological and ultrastructural characteristics pentastomids were identified as Raillietiella orientalis. Additionally, this species identification was confirmed by DNA sequencing (18S rRNA).Pentastomid-infected insects, such as cockroaches, might play an important role in the transmission of R. orientalis as suitable obligate intermediate hosts. Another crucial factor to be considered is the importation of wild caught individuals, providing a potential source for numerous emerging infectious disease transmissions and parasite spillovers.This is the first report, to the best of our knowledge, on a patent pulmonary R. orientalis infection in a captive chameleon. We call for further investigations on neglected pentastomid infections in chameleons and lizards kept as pets to better understand implications of this new host record and its possible role in transmission of emerging pentastomiasis.